DA COESÃO À ENUNCIAÇÃO: ASPECTOS DE TEXTUALIDADE EM UM CORPUS DE TEXTOS DE QUÍMICA - Finatto, Maria José Bocorny; Azeredo, Susana de (Intercâmbio, 2010)
This paper presents some results of an interdisciplinary research focused on the function of connectors used to introduce paraphrase utterances. The corpus selected is composed of Chemistry handbooks translated from English (SL) into Portuguese (TL). This paper also intends to show, through a contrastive analysis between SL (the source language) and TL (the target language), the importance not only of critical production about translation conditions of handbooks, but also of some principles from the area of corpus linguistics analysis.